RACK1 Controls IRES-Mediated Translation of Viruses. - Majzoub, K.; Hafirassou, M.L.; Meignin, C.; Goto, A.; Marzi, S.; Fedorova, A.; Verdier, Y.; Vinh, J.; Hoffmann, J.A.; Martin, F.; Baumert, T.F.; Schuster, C.; et al. (Cell, 2014)
Fighting viral infections is hampered by the scarcity of viral targets and their variability, resulting in development of resistance. Viruses depend on cellular molecules-which are attractive alternative targets-for their life cycle, provided that they are dispensable for normal cell functions. Using the model organism Drosophila melanogaster, we identify the ribosomal protein RACK1 as a cellular factor required for infection by internal ribosome entry site (IRES)-containing viruses. We further show that RACK1 is an essential determinant for hepatitis C virus translation and infection, indicating that its function is conserved for distantly related human and fly viruses. Inhibition of RACK1 does not affect Drosophila or human cell viability and proliferation, and RACK1-silenced adult flies are viable, indicating that this protein is not essential for general translation. Our findings demonstrate a specific function for RACK1 in selective mRNA translation and uncover a target for the development of broad antiviral intervention.